Ergogenic aids and nutritional supplementation on athletic performance and exercise recovery in competitive athletes: a systematic literature review - Jeki Haryanto; Japhet Ndayisenga; Dally Rahman; Fiky Zarya (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The widespread use of ergogenic aids and nutritional supplements among competitive athletes has generated extensive research, yet findings remain fragmented due to heterogeneous methodologies, inconsistent outcomes, and diverse populations. This systematic literature review (SLR) synthesized empirical evidence on the effects of ergogenic aids and dietary supplementation on athletic performance and recovery, identified dominant themes, and highlighted research gaps. Following PRISMA 2020 guidelines, a systematic search of the Scopus database was conducted on 7 June 2026 using terms related to ergogenic aids, nutritional supplementation, performance, and recovery. Of 675 records published between 2017 and 2026, 34 duplicates were removed and screening based on predefined criteria yielded 25 studies for thematic synthesis. Study quality was appraised using the FICO framework (Focus–Information–Context–Outcome), and findings were integrated via thematic synthesis rather than meta-analysis owing to substantial heterogeneity in supplement types, dosing, and outcome measures. Three thematic clusters emerged: (1) protein and macronutrient supplementation enhanced muscle protein synthesis and reduced exercise-induced muscle damage, particularly with leucine-enriched and post-exercise protocols; (2) caffeine, creatine, beta-alanine, nitrates, and polyphenolic antioxidants consistently improved high-intensity performance, endurance, and oxidative stress profiles; and (3) multi-ingredient pre-workout and periodized nutrition strategies produced synergistic recovery benefits, although dose-response relationships and population-specific effects remain unclear. Findings advance mechanistic understanding and support evidence-based nutritional protocols while emphasizing the need for individualized supplementation strategies informed by metabolomics, genomics, and microbiome profiling.